Metastatic Papillary Gallbladder Carcinoma with a Unique Presentation and Clinical Course - Chapman, Brandon C; Jones, Teresa; McManus, Martine C; Shah, Raj; Gajdos, Csaba (JOP. Journal of the Pancreas, 2014)
Context Papillary gallbladder adenocarcinoma (PGA) represents 5% of malignant gallbladder tumors. Metastatic disease frequently involves lymph nodes or other structures in the hepatoduodenal ligament. Case report A Fifty-nine-year-old female with right upper quadrant pain and a giant gallbladder on ultrasound was found to have a segment 6 liver lesion during an attempted laparoscopic cholecystectomy. After appropriate staging, she underwent an open cholecystectomy and extended right hepatic lobectomy with portal lymph node dissection. Pathology demonstrated well-to-moderately differentiated PGA with identical morphology and immunohistochemistry in the liver resection specimen with negative margins. Despite adjuvant chemotherapy, she developed increased uptake in the head of the pancreas on PET scan. Endoscopic ultrasound with fine needle aspiration demonstrated metastatic PGA. She underwent an attempted Whipple operation but due to repeatedly positive pancreatic duct margins, she ended up with a total pancreatectomy and splenectomy. Final pathology showed metastatic PGA along the entire length of the pancreatic duct with only a single focus of tumor invasion into the pancreatic parenchyma. She developed a new liver metastases six months later that was unresponsive to FOLFOX therapy and she died of metastatic disease 33 months from her initial diagnosis. Conclusion To our knowledge, this is the first report of metastatic PGA recurring along the entire pancreatic duct with disease confined to the pancreas only. We hypothesize that papillary tumor cells spread to pancreatic duct via the common bile duct and remained dormant for several years. An aggressive surgical approach may prolong survival in well-selected patients with PGA’s. Image: Metastatic papillary gallbladder adenocarcinoma with positive CK20 staining.